Is there a need for anthropometric standards in olympic sports? A proposal for the kinanthropometric profile of elite flag football athletes - Luis Felipe Talavera-Hernández; Claudia Maceroni; Eleanor Louise Travis-Carr; Lewis James Macgregor; Luis Gerardo Vázquez-Villarreal; Rubén Menargues-Ramírez; Martha Patricia Dergal-Irigoyen; Elizabeth Reyes-Castillo; Jesús Iván Castro-Ávila; José Miguel Martínez-Sanz; Nidia Rodriguez-Sanchez (Frontiers in Nutrition)
BackgroundBody composition strongly influences the performance of flag football (FF) players, which makes anthropometric measurements important. With the growing popularity of FF, understanding body composition requirements for both male and female players is essential to help optimize their performance. Purpose: This study aimed to characterize and compare anthropometric and body composition profiles between male and female FF players across different playing positions. The study was conducted during the European Flag Football Championship organized by the International Federation of American Football (IFAF).MethodsA cross-sectional study design was used. Anthropometric measurements followed the International Society for the Advancement of Kinanthropometry (ISAK) full profile protocol. Data were collected from 91 male and 48 female players, and body composition was estimated using the five-way fractionation method. Comparisons between males and females were performed using analysis of variance (ANOVA), with statistical significance set at p < 0.05.ResultsNormative reference values and percentiles for anthropometric variables and body composition were established for male and female FF athletes. Male players had an average sum of eight skinfolds of 83.5 ± 30.5 mm, muscle mass of 36.0 ± 7.4 kg, and adipose mass of 19.8 ± 5.1 kg. Female players (27.4 ± 4.5 years) had an average sum of 8 skinfolds of 115.5 ± 40.9 mm, muscle mass of 27.8 ± 4.0 kg, and adipose mass of 20.5 ± 4.8 kg. Both sexes predominantly presented a mesomorphic somatotype.ConclusionThis study provides valuable data on anthropometric characteristics of male and female FF players. These results can help create normative reference values and support strategies for performance optimization. Additionally, findings contribute to better understanding of body composition needs in FF athletes of both sexes.